Metabolomics analyses reveal the crucial role of ERK in regulating metabolic pathways associated with the proliferation of human cutaneous T‐cell lymphoma cells treated with Glabridin - Abdul Q. Khan (14153247) (2024)
Cutaneous T‐cell lymphomas (CTC) are a heterogeneous group of T‐cell lymphoproliferative malignancies of the skin with limited treatment options, increased resistance and remission. Metabolic reprogramming is vital in orchestrating the uncontrolled growth and proliferation of cancer cells. Importantly, deregulated signalling plays a significant role in metabolic reprogramming. Considering the crucial role of metabolic reprogramming in cancer‐cell growth and proliferation, target identification and the development of novel and multi‐targeting agents are imperative. The present study explores the underlying mechanisms and metabolic signalling pathways associated with Glabridin mediated anti‐cancer actions in CTCL. Our results show that Glabridin significantly inhibits the growth of CTCL cells through induction of programmed cell death (PCD) such as apoptosis, autophagy and necrosis. Interestingly, results further show that Glabridin induces PCD in CTCL cells by targeting MAPK signalling pathways, particularly the activation of ERK. Further, Glabridin also sensitized CTCL cells to the anti‐cancer drug, bortezomib. Importantly, LC–MS‐based metabolomics analyses further showed that Glabridin targeted multiple metabolites and metabolic pathways intricately involved in cancer cell growth and proliferation in an ERK‐dependent fashion. Overall, our findings revealed that Glabridin induces PCD and attenuates the expression of regulatory proteins and metabolites involved in orchestrating the uncontrolled proliferation of CTCL cells through ERK activation. Therefore, Glabridin possesses important features of an ideal anti‐cancer agent. Other Information Published in: Cell Proliferation License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/cpr.13701